Pathological gambling: a review of the neurobiological evidence relevant for its classification as an addictive disorder - Fauth-Bühler, Mira; Mann, Karl; Potenza, Marc N. (Addiction biology, 2017)
In light of the upcoming eleventh edition of the International Classification of Diseases (ICD-11), the question arises as to the most appropriate classification of ‘Pathological Gambling’ (‘PG’). Some academic opinion favors leaving PG in the ‘Impulse Control Disorder’ (‘ICD’) category, as in ICD-10, whereas others argue that new data especially from the neurobiological area favor allocating it to the category of ‘Substance-related and Addictive Disorders’ (‘SADs’), following the decision in the fifth revision of the Diagnostic and Statistical Manual of Mental Disorders. The current review examines important findings in relation to PG, with the aim of enabling a well-informed decision to be made with respect to the classification of PG as a SAD or ICD in ICD-11. Particular attention is given to cognitive deficits and underlying neurobiological mechanisms that play a role in SADs and ICDs. These processes are impulsivity, compulsivity, reward/punishment processing and decision-making. In summary, the strongest arguments for subsuming PG under a larger SAD category relate to the existence of similar diagnostic characteristics; the high co-morbidity rates between the disorders; their common core features including reward-related aspects (positive reinforcement: behaviors are pleasurable at the beginning which is not the case for ICDs); the findings that the same brain structures are involved in PG and SADs, including the ventral striatum. Research on compulsivity suggests a relationship with PG and SAD, particularly in later stages of the disorders. Although research is limited for ICDs, current data do not support continuing to classify PG as an ICD.